Deep-aea reef building Farreidae (Porifera; Hexactinellida) from the Bering Sea - Tabachnick, Konstantin R.; Menshenina, Larisa L. (Zootaxa, 2026)
Hexactinellid sponges play an important role as ecosystem engineers through the formation of sponge reefs. Five representatives of the reef building genus Farrea (Farreidae) are recorded from the slope of the Piip Volcano (Volcanologists Massif, the Bering Sea). One of them, F. aspondyla was previously known from the North Pacific. Here we describe four new species of this genus: F. piipi; F. koltuni; F. reiswigi and F. ptushkini. These sponges are important in the sponge reef construction in the bathyal zone of the Bering Sea.